Spectral characteristics of the polarization-manipulated signals - P. V. Anikin; D. N. Jamanov (Научный вестник МГТУ ГА, 2016)
The article describes the method of analysis of the spectral characteristics of the polarization- manipulated signals with a continuous change in the angle of ellipticity . Features of the spectral analysis of such signals are defined. Need of the full spectral analysis of two-dimensional signals is considered. The received results allow to estimate redistribution of energy between harmonious components (taking into account their polarizing structure) at change of size of deviation of a corner of ellipticity.Keywords: full spectral analysis, the polarizing manipulated signals with continuous change of a corner of ellipticity, polarizing structure of signals.